PENYELESAIAN SENGKETA OBJEK JAMINAN FIDUSIA DALAM HAL DEBITUR WANPRESTASI PADA PT. BPR KRISNA YUNA DANA DI GIANYAR - Yudhi Sutrisna, Gede; Rudy, Dewa Gde; Dharma Kusuma, A. A. Gede Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013, 2013)
Banks in providing credit to make the binding fiduciary with fiduciary deed notarized and then registered by the fiduciary registration . However, because the registration does not expressly include a deadline until when the fiduciary deed registered , then sometimes in practice, many creditors are no longer register the warranty deed fidusianya tersebut.Oleh fieldwork was conducted at PT . RB Krishna Yuna Fund to learn about solving problems if the debtor with a fiduciary breach . The issues discussed in this paper , namely : whether the creditor can execute the fiduciary holder object warranty by parate execution when the debtor defaults , and how the process execution objects fiduciary if the debtor defaults on PT . RB Krishna Yuna Fund . The method used in this paper is by using the method of empirical legal research where research is done because there is a gap between the law ( das solen ) and the reality on the ground (das Dein) . Results Of Research Done Fiduciary Based Execution Objects In This Parate Execution Debtor Defaults On PT . RB Krishna Yuna is the Creditor Fund fiduciary holder can execute security objects by parate execution when the debtor defaults . This is because the debtor fiduciary holder serves as a secure creditor has the right to take precedence over debt repayment . At PT . RB Krishna Yuna Fund , binding fiduciary implemented using notarized deed made before a notary , where this deed also have binding legal force as court decisions . At PT . RB Krishna Yuna Fund , in the event of default settlement is not done with parate execution . However, if there is problems then settled through kinship . By doing sales directly by the debtor objects fiduciary , or assisted by the bank .
Keywords: Fiduciary transfer of ownership,Parate Execution, Defaults